Maturation and germination of Trichosanthes cucumerina L. seeds - Silva,Lorena de Souza (2022)
Abstract: Trichosanthes cucumerina L. (Cucurbitaceae) is a traditional fruit vegetable grown by family farmers in the Amazon. This study aimed to evaluate seed maturation as a function of age and fruit morphological characteristics, and the effect of different temperatures on seed germination of accessions of the species. A completely randomized design was adopted in the maturation study, with five treatments (fruit age: 20, 30, 40, 50, and 60 days after anthesis - DAA) and four replications. Seed quality was evaluated through dry mass, water content, germination, and vigor variables, while the fruits were evaluated for physical characteristics and the number of seeds. A completely randomized design in a 3 (temperatures: 20, 25, and 30 °C) x 7 (accessions: PIN I, PIN II, TSA, MAO, UTB, ITA, and IMI) factorial scheme, with four replications was adopted in the study of germination temperatures. Seed quality was evaluated using germination and vigor tests. Seeds reach physiological maturity around 50 DAA. The fruits are partially or completely orange or reddish-orange in color at that time. The temperature of 30 °C favored the seed germination process, resulting in a higher percentage and germination rate.